2022
DOI: 10.1038/s41374-021-00669-4
|View full text |Cite
|
Sign up to set email alerts
|

Advanced detection strategies for cardiotropic virus infection in a cohort study of heart failure patients

Abstract: The prevalence and contribution of cardiotropic viruses to various expressions of heart failure are increasing, yet primarily underappreciated and underreported due to variable clinical syndromes, a lack of consensus diagnostic standards and insufficient clinical laboratory tools. In this study, we developed an advanced methodology for identifying viruses across a spectrum of heart failure patients. We designed a custom tissue microarray from 78 patients with conditions commonly associated with virus-related h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 69 publications
0
7
0
1
Order By: Relevance
“…Viral genome was detected in 38% of patients, and 93% of these patients had a prior history of viral infection, whereas only 3 out of 215 control samples derived from patients with no recent history of viral infection or myocarditis were positive for viral genome (Bowles et al, 2003). It was also reported that viral RNA could be detected in 46.4% of clinically diagnosed group of 69 heart failure patients in Canada (Hanson et al, 2022). On the other hand, 20% of patients suffering from DCM were positive for viral genomes in their heart samples, and 7% of these patients had a confirmed diagnosis of prior viral infection (Bowles et al, 2003), suggesting that not all viral infections are successfully eliminated, which may lead to low grade levels of inflammation, engagement of immune system, or, in some cases, disease.…”
Section: Viral Infection Of the Heart -A Question Of Persistencementioning
confidence: 97%
See 1 more Smart Citation
“…Viral genome was detected in 38% of patients, and 93% of these patients had a prior history of viral infection, whereas only 3 out of 215 control samples derived from patients with no recent history of viral infection or myocarditis were positive for viral genome (Bowles et al, 2003). It was also reported that viral RNA could be detected in 46.4% of clinically diagnosed group of 69 heart failure patients in Canada (Hanson et al, 2022). On the other hand, 20% of patients suffering from DCM were positive for viral genomes in their heart samples, and 7% of these patients had a confirmed diagnosis of prior viral infection (Bowles et al, 2003), suggesting that not all viral infections are successfully eliminated, which may lead to low grade levels of inflammation, engagement of immune system, or, in some cases, disease.…”
Section: Viral Infection Of the Heart -A Question Of Persistencementioning
confidence: 97%
“…Adenovirus type 8 was detected in 17.4% of patients ( n = 23) suffering from acute idiopathic DCM, which was severe enough to require a heart transplant ( Hosseini et al, 2018 ). A recent study by Hanson et al in Canada revealed that adenovirus was detected in 19 out of 69 (27.5%) patients suffering from heart failure ( Hanson et al, 2022 ). A study by Bowles et al conducted in the United States showed that 142 out of 624 (23%) patients with myocarditis, and 18 out of 149 (12%) patients with DCM had adenovirus in their heart tissues ( Bowles et al, 2003 ).…”
Section: Adenovirusmentioning
confidence: 99%
“…[ 2 ] HF poses a significant burden on public health with substantial costs owing to the high risk of morbidity and mortality. [ 3 ] HF treatment is primarily supportive and includes standard heart failure medications, mechanical aids, and heart transplantation; although medications and surgery can alleviate the symptoms of HF, these approaches do not completely cure HF, [ 4 ] non-pharmacologic treatments to alleviate the symptoms of HF must be identified.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that up to 40% of DCM is associated with in ammation or viral infections [9,10]. Scientists have detected viruses including Coxsackievirus B3 (CVB3), Adenovirus 2(ADV2), Enterovirus (EV), Human Cytomegalovirus (HCMV), Epstein-Barr virus (EBV), Hepatitis C and E, Parvovirus B19 (PVB19), Human Herpesvirus 6 (HHV-6) and In uenza B in donated myocardial tissue from patients with DCM [9,11]. Besides, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can directly cause myocardial-speci c injury by upregulation of ACE2 in cardiomyocytes [12], or indirectly damage the myocardium via "cytokinemediated cardiotoxicity" and "triggering autoimmune reactions in the heart" [13].…”
Section: Introductionmentioning
confidence: 99%
“…VMC is an important cause of HF and sudden cardiac death in young healthy adults, as well as an etiological precursor of DCM [8]. Studies have shown that up to 40% of DCM is associated with in ammation or viral infections [9,10]. Scientists have detected viruses including Coxsackievirus B3 (CVB3), Adenovirus 2(ADV2), Enterovirus (EV), Human Cytomegalovirus (HCMV), Epstein-Barr virus (EBV), Hepatitis C and E, Parvovirus B19 (PVB19), Human Herpesvirus 6 (HHV-6) and In uenza B in donated myocardial tissue from patients with DCM [9,11].…”
Section: Introductionmentioning
confidence: 99%